2011
DOI: 10.2967/jnumed.110.086645
|View full text |Cite
|
Sign up to set email alerts
|

O-(2-18F-Fluoroethyl)-L-Tyrosine PET Predicts Failure of Antiangiogenic Treatment in Patients with Recurrent High-Grade Glioma

Abstract: The objective of this study was to compare MRI response assessment with metabolic O-(2-18 F-fluoroethyl)-L-tyrosine ( 18 F-FET) PET response evaluation during antiangiogenic treatment in patients with recurrent high-grade glioma (rHGG). Methods: Eleven patients with rHGG were treated biweekly with bevacizumab-irinotecan. MR images and 18 F-FET PET scans were obtained at baseline and at follow-up 8-12 wk after treatment onset. MRI treatment response was evaluated by T1/T2 volumetry according to response assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
109
0
8

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(124 citation statements)
references
References 26 publications
7
109
0
8
Order By: Relevance
“…Responders based on 18 F-FDOPA PET data survived 3.5 times longer (12.1 months vs. 3.5 months of median overall survival) than nonresponders, which was much higher than responders based solely on MRI (90). Similar results have been reported for 18 F-FET (92)(93)(94).…”
supporting
confidence: 77%
“…Responders based on 18 F-FDOPA PET data survived 3.5 times longer (12.1 months vs. 3.5 months of median overall survival) than nonresponders, which was much higher than responders based solely on MRI (90). Similar results have been reported for 18 F-FET (92)(93)(94).…”
supporting
confidence: 77%
“…The threshold also yielded a good discriminative power to separate prognostic groups in terms of progression-free and overall survival [14]. Hutterer et al [27] reported a decrease of 45% of MTV to define metabolic response in recurrent high-grade glioma patients treated with bevacizumab and irinotecan. For 18 F-FLT PET, more than 25% reduction in tumor SUV uptake was defined as a metabolic response in patients with recurrent malignant gliomas treated with bevacizumab and irinotecan [28].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the fluorinated amino acid analog 18 F-FET has emerged as a powerful complementary tool for glioma imaging (21,22). 18 F-FET PET was shown to be useful for biopsy and treatment planning by accurate delineation of the tumor borders and demarcation of most malignant tumor parts (11,21,(23)(24)(25) and for subsequent treatment monitoring including differentiation between benign therapyinduced changes and tumor recurrence (13,18,(26)(27)(28). Furthermore, the additional use of kinetic analysis of 18 F-FET PET was shown to enable more accurate tumor grading, even in individual patients: increasing time-activity curves are considered to be associated with less malignant low-grade glioma tissue, whereas decreasing timeactivity curves were shown to be prevalent in more aggressive high-grade glioma tissue (9,10).…”
Section: Discussionmentioning
confidence: 99%